Consumer Preferences and Willingness to Pay for Cigarette Products in Indonesia - Yafi, Muhammad Ali; Wardania, Nastiti; Maharani, Mutiara Ria Despita; Thohir, Nada Sofiyyah Van; Adyanti, Amanda Sekar; Mohammed, Ethar Hassan (Department of Social Economy, Faculty of Bio-Industry, Agriculture and Forestry, University of Brawijaya, 2026)
Purpose: The consumption of cigarettes in Indonesia has been increasing on an annual basis. A shift in consumer preferences with regard to the purchasing of cigarettes has been observed. The government of Indonesia has the capacity to regulate the purchase of cigarettes with the objective of controlling cigarette consumption. The objective of study is to analyse cigarette consumer preferences in Indonesia and to ascertain the willingness of cigarette consumers in Indonesia to pay. Design/Methodology/Approach: The study utilised data from an online questionnaire, with a total 101 respondents. The questionnaire incorporated five attributes: type, content, taste, number of sticks, and price. The analysis employed was Discrete Choice Experiment (DCE) analysis through the stages of attribute identification and choice set construction. Findings: The findings were derived from the calculation of conditional logistic regression, wherein the attributes of content, taste, and number of sticks exhibited positive utility values, while the attributes of type and price demonstrated negative utility values. Consumer preferences were found to be oriented towards cigarette products that were characterised by filter type, mild content, original taste, and a pack size of 12 sticks. An increase in price was found to result in a decrease in consumption. A survey of consumer spending habits revealed that the following prices were considered affordable: Rp 34,777 for kretek cigarettes, Rp 37,045 for mild cigarettes, Rp 59,479 for original cigarettes, and Rp 46,282 for 16 sticks. The findings of this study indicate that producers can develop product strategies aligned with consumer preferences and willingness to pay, thereby enhancing market competitiveness and better targeting consumer demand. Originality/Value/Novelty: The novelty of this study lies in providing a comprehensive understanding of the cigarette attributes that are the top priorities for cigarette consumers in Indonesia when making purchasing decisions, using the DEC approach, and their willingness to pay for cigarette products, as measured by Willingness To Pay (WTP).